First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female - Kumar, Hirdesh; Chandra, Kailash (Zootaxa, 2020)
Orthelimaea himalayana (Ingrisch, 1990) is recorded for the first time from India and its female is also described first time from Central Himalaya. A key to Indian species of Orthelimaea Karny, 1926 is also provided.